Barley β-glucan inhibits digestion of soybean oil in vitro and lipid-lowering effects of digested products in cell co-culture model. (February 2023) - Li, Jiaying; Zhou, Yurong; Zhang, Jiayan; Cui, Ling; Lu, Haina; Zhu, Ying; Zhao, Yansheng; Fan, Songtao; Xiao, Xiang
Graphical abstract: Highlights: The structure of β-glucan in barley changed after fermentation by L. plantarum dy-1. β-glucan in fermented barley could inhibit digestion and absorption of soybean oil. The lipid deposition decreased by adding the β-glucan from fermented barley. The lipid-lowering activity of β-glucan in barley was enhanced after fermentation. Abstract: The effect of barley β-glucan on soybean oil digestion characteristics before and after fermentation was studied in an in vitro –simulated gastrointestinal digestion model. The addition of barley β-glucan made the system more unstable, the particle size increased significantly, and confocal laser imaging showed that it was easier to form agglomerates. The addition of barley β-glucan increased the proportion of unsaturated fatty acids in digestion products, and reduced digestibility of soybean oil. In a co-culture model of Caco-2/HT29 and HepG2 cells, the effects of digestive products of soybean oil and barley β-glucan before and after fermentation on lipid metabolism in HepG2 cells were investigated. The results showed that adding only soybean oil digestion products significantly increased triglycerides (TG) content and lipid accumulation in basolateral HepG2 cells. When fermented barley β-glucan was added, lipid deposition was significantly decreased, and the lipid-lowering activity was better than that of unfermented barley β-glucan.